Analysis of Sales Volume Through Purchase Intention Considering the Influence of Price, Discounts, and Shipping Costs - Suwarna, Roy Adi; Astuti, Miguna; Yulivan, Ivan; Triwardhani, Diana (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the influence of price, discounts, and shipping costs on sales volume through purchase intention at an authorized Daikin AC dealer in Banten. Data were collected via questionnaires from 173 respondents and analyzed using SmartPLS 4.0. The findings indicate that price, discounts, and shipping costs significantly affect sales volume both directly and through purchase intention. Hypothesis testing results reveal that price, discounts, and shipping costs have a positive effect on sales volume, with t-statistics of 5.43, 4.67, and 3.95, respectively. Moreover, purchase intention as a mediating variable significantly influences sales volume, with a t-statistic of 6.12. The managerial implications suggest that marketing managers should set competitive prices, design attractive discount programs, and optimize shipping costs to enhance purchase intention and increase sales volume. This study contributes to the marketing management literature by providing empirical evidence on the impact of price, discounts, and shipping costs on sales volume through purchase intention. The findings serve as a valuable reference for researchers and business practitioners in refining marketing strategies.